Comment on “Genetic variants and source of introduction of SARS-CoV-2 in South America” - Romero P.E. (2021)
I read with great interest a recent study by Poterico and Mestanza who described mutations in 30 SARS‐CoV‐2 genomes from South American countries (Argentina, Brazil, Chile, Colombia, Ecuador, and Peru). Next‐generation sequencing (NGS) technologies have accelerated genomic and metagenomic studies providing affordable tools to obtain pathogen genomes and improving diagnosis and surveillance efforts. However, many downstream analyses after assembling the genomes are impacted by low‐quality sequences and sequence contamination, which could lead to wrong conclusion.